Combined treatment of high and very high risk prostate cancer: results of neoadjuvant treatment - A. V. Troyanov; V. A. Biryukov; I. V. Zaborsky; V. S. Chaykov; I. O. Dementev; E. O. Shchukina; O. B. Karyakin (Исследования и практика в медицине, 2023)
Purpose of the study. Assessment of safety and short‑term effectiveness of high and very high‑risk prostate cancer neoadjuvant chemo‑ hormonal treatment without distant metastases.Patients and methods. Combined hormone chemo‑ radiation treatment of 33 patients with prostate cancer of high and very high risk of progression without distant metastases was performed. Metastases to regional lymph nodes were found in 9 patients according to the examination data (MRI, MSCT), no metastases were detected in 24 patients. All patients underwent combined chemohormonal therapy in the amount of 4 courses of docetaxel intravenously at a dose of 75 mg/m2 every 3 weeks as the first stage of treatment. in combination with androgen deprivation therapy with agonists or antagonists of GnRH before performing radical radiation therapy (combined or remote). All patients underwent neoadjuvant hormone therapy: 16 patients – with the use of GnRH antagonists (Degarelix), 17 – with the use of GnRH agonists (Gozerelin/Leuprorelin/Triptorelin). The toxicity of the presented treatment regimen and its immediate effectiveness – the effect on the level of prostate‑s pecific antigen (PSA), prostate volume, and the quality of urination – were evaluated.Results. Treatment regimen was highly effective concerning PSA decrease (from initial median level 79,67 ng/ml to 1,45 ng/ml after neoadjuvant treatment), all subjects responded well, no non‑responders observed. Median prostate volume decreased from 44 cm3 to 25 cm3 after treatment, which guaranteed availability and safety of further radical radiation treatment. Urinary function was restored in all subject with initial urinary retention.Conclusion. Neoadjuvant chemo‑h ormonal treatment was highly effective in PSA level, prostate volume decrease and functional results improvement which secured further radical radiation treatment in one of its types. Toxicity was acceptable, adverse events did not exceed grade II in most cases and did not lead to treatment discontinuation in any cases, while quality of life remained high enough.